2020
DOI: 10.1038/s41598-020-60394-8
|View full text |Cite
|
Sign up to set email alerts
|

Sub-oxycline methane oxidation can fully uptake CH4 produced in sediments: case study of a lake in Siberia

Abstract: it is commonly assumed that methane (cH 4) released by lakes into the atmosphere is mainly produced in anoxic sediment and transported by diffusion or ebullition through the water column to the surface of the lake. In contrast to that prevailing idea, it has been gradually established that the epilimnetic cH 4 does not originate exclusively from sediments but is also locally produced or laterally transported from the littoral zone. Therefore, CH 4 cycling in the epilimnion and the hypolimnion might not be as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
(53 reference statements)
5
15
0
Order By: Relevance
“…For example, aerobic and anaerobic methanotrophic communities in the water column are dynamic and may rapidly respond to shifting CH 4 , O 2 , and other electron acceptor concentrations (Graf et al 2018;Rissanen et al 2020;Mayr et al 2020b). Stratified lakes may have sufficiently high rates of CH 4 oxidation at or near the oxycline (Morana et al 2015) or in the anaerobic water column (Thalasso et al 2020; van Grinsven et al 2020a) to compensate for potentially low oxidation efficiency in sediments. Low sediment oxidation efficiency may be a less important control on emissions during seasonal overturn of stratified lakes, which can be a hot moment for CH 4 oxidation in the water column (Kankaala et al 2007;Mayr et al 2020a).…”
Section: Comparing Ch 4 Production and Oxidationmentioning
confidence: 99%
“…For example, aerobic and anaerobic methanotrophic communities in the water column are dynamic and may rapidly respond to shifting CH 4 , O 2 , and other electron acceptor concentrations (Graf et al 2018;Rissanen et al 2020;Mayr et al 2020b). Stratified lakes may have sufficiently high rates of CH 4 oxidation at or near the oxycline (Morana et al 2015) or in the anaerobic water column (Thalasso et al 2020; van Grinsven et al 2020a) to compensate for potentially low oxidation efficiency in sediments. Low sediment oxidation efficiency may be a less important control on emissions during seasonal overturn of stratified lakes, which can be a hot moment for CH 4 oxidation in the water column (Kankaala et al 2007;Mayr et al 2020a).…”
Section: Comparing Ch 4 Production and Oxidationmentioning
confidence: 99%
“…Traditionally, the net CH 4 production is determined by archaeal methanogenesis, which produces methane as an end product of organic matter degradation in anoxic conditions, and to methanotrophs, which consume it in oxic conditions (Schubert and Wehrli, 2018). In freshwater ecosystems, the anoxic sediments are a primary source of CH 4 (Segers, 1998), where methanogens are very sensitive to temperature and quantity and quality of the organic matter used as substrate (Marotta et al, 2014;Rasilo et al, 2015;Sepulveda-Jauregui et al, 2018;Thanh-Duc et al, 2010;West et al, 2012;Yvon-Durocher et al, 2014). They are also affected by the extent of anoxia in the sediments insomuch as they are obligate anaerobes and will not survive and produce CH 4 under aerobic conditions (Chistoserdova et al, 1998;Schubert and Wehrli, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…6). A recent study by Thalasso et al (2020) found that, in a stratified lake in north-central Siberia, all CH4 produced in the sediments and deep hypolimnion was removed below the oxycline, suggestive of high AOM. This case study suggests, in northern lakes that stratify, it is possible for most or all CH4 produced in sediments to be anaerobically oxidized in the hypolimnion, resulting in little to no CH4 exchange with the epilimnion and/or atmosphere.…”
Section: Methane Oxidationmentioning
confidence: 96%